Usability Analysis of Pornography Detection System on Internet Users using Mc’Calls Method - Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2017)
At this time there are several tools used to prevent a pornography, the most common one is nawala project that use filtering method in DNS, based on Keyword and Image. This method has a weakness, because it could be wrong, when a researcher or lecturer of science and technology need the information about “sex”, the keyword automatically can’t be access. Even at this time the maker of pornography sites already so intelligent, they give the sites name which is doesn’t have any correlation with pornography. Based on that reason, we proposed a Software quality testing with subject, usability analysis of pornography detection system on internet users using quality factor of Mc Call’s which combine the operability and training matrix as a means to determining the quality of software.